Precursor ceramic adhesive repairing agent as well as preparation method and repairing method thereof
By using the front -drive ceramic glue adhesive, the combination of PMHS, D4VI, and nano TIB2 solves the problem of poor toughness of ceramic materials and a single existing repair method, and realizes the efficient repair of ceramic materials and the recovery of mechanical properties.
Patent Information
- Application Number
- CN202411522318.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
Ceramic materials have poor toughness and are prone to cracks and damage. The existing ceramic repair method is single and the repair effect is limited, making it difficult to effectively restore the mechanical properties of the material.
The front -drive ceramic glue adhesive is used. The repair agent consists of PMHS, D4VI and nano TIB2. The heat treatment is transformed from a liquid phase to a solid phase, thereby filling and repairing the defects of ceramic materials.
The universal repair of ceramic materials is realized, its mechanical performance is effectively restored, the service life is extended and reliability is improved.
Smart Images

Figure CN119371232A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material repair, and in particular relates to a precursor ceramic adhesive repair agent, a preparation method thereof and a repair method thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Ceramic materials have the advantages of high hardness, good wear resistance, good chemical stability and low price. Therefore, ceramic materials play an important role in the field of modern mechanical processing. However, ceramic materials have poor toughness and are prone to cracks and breakage during use, reducing the reliability and service life of the material.
[0004] In order to reduce the impact of the brittleness of ceramic materials on their performance, on the one hand, the toughness of the material is enhanced to reduce the harm caused by brittleness; on the other hand, the damaged parts of the material are repaired to extend its service life.
[0005] The current research on ceramic repair mainly relies on adding substances that easily react with oxygen at high temperatures to the material, and filling and repairing the damaged area through oxidation products. However, this ceramic repair method is relatively simple and the repair effect is limited. It is only suitable for repairing defects in smaller areas. In addition, adding repair materials to the matrix material may lead to a decrease in material performance, reducing the service life and reliability of the material. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a precursor ceramic adhesive repair agent, a preparation method and a repair method thereof. By repairing ceramic materials with the repair agent, defects in ceramic tool materials can be universally repaired, the mechanical properties of ceramic materials can be effectively restored, and their service life and reliability can be improved.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In the first aspect, the present invention provides a precursor ceramic adhesive repair agent, which is composed of the following components by weight: PMHS 25-75 parts, D 4 Vi 25-75 parts, nano TiB 2 12-38 servings.
[0009] PMHS is polymethylhydrogensiloxane; D 4 Vi is tetramethyltetravinylcyclotetrasiloxane.
[0010] PMHS and D 4 Vi is the matrix material of the repair agent, TiB 2It is a filler for repair agents. The function of the repair agent matrix is to realize the transformation of the repair agent from liquid phase to solid phase and from organic to inorganic through universal cross-linking, curing and pyrolysis reaction, so as to fill and repair defects such as cracks. 2 It can reduce the volume shrinkage of the repair agent and improve its ceramic yield and repair performance.
[0011] In some embodiments, the precursor ceramic adhesive repair agent comprises the following components by weight: 30-60 parts of PMHS, D 4 Vi 30-60 parts, nano TiB 2 15-35 servings.
[0012] Preferably, the precursor ceramic adhesive repair agent comprises the following components by weight: 30-50 parts of PMHS, D 4 Vi 30-50 parts, nano TiB 2 15-30 servings.
[0013] Further preferably, the precursor ceramic adhesive repair agent comprises the following components by weight: 35-45 parts of PMHS, D 4 Vi 35-45 parts, nano TiB 2 15-25 servings.
[0014] More preferably, the precursor ceramic adhesive repair agent comprises the following components by weight: 40 parts of PMHS, D 4 Vi 40 parts, nano TiB 2 20 servings.
[0015] In some embodiments, the number average molecular weight of PMHS is 1700-3200; TiB 2 The average particle size of the powder is 40 nm.
[0016] The number average molecular weight of PMHS is 1700-3200, the purity is 98.5%, and the hydrogen content is 1.6%; 4 The purity of Vi is 95% and the density is 0.997g / ml; TiB 2 The average particle size of the powder is 40nm and the purity is greater than 99%.
[0017] TiB 2 The particle size of the powder cannot be too large. If the particle size is too large, the cracks in the ceramic material will be 2 The inability of particles to enter will cause significant volume shrinkage at the repaired location, which will affect the mechanical properties after the repair.
[0018] In a second aspect, the present invention provides a method for preparing the precursor ceramic adhesive repair agent, comprising the following steps:
[0019] PMHS and D 4 Vi are mixed evenly according to the proportion to obtain a matrix mixed liquid;
[0020] Add nano-TiB to the matrix mixture 2 , mix well to get the repair agent.
[0021] In a third aspect, the present invention provides a repair method using the precursor ceramic adhesive repair agent, comprising the following steps:
[0022] The repairing agent is applied to the repaired position of the ceramic workpiece to be repaired, so that the repairing agent penetrates into the damaged interior; and then the workpiece to be repaired is heat treated to complete the repair;
[0023] The heat treatment process is: heating to 250-325°C at a rate of 2-4°C / min and keeping the temperature for 15-75min; after the temperature is kept, heating to 800-1500°C at a rate of 4-8°C / min and keeping the temperature for more than 60min.
[0024] At around 300°C, PMHS and D4Vi will undergo a cross-linking and curing reaction, and the original mixed solution will change from liquid to solid (or gel), but the performance is poor;
[0025] As the temperature rises, the solid material will undergo a pyrolysis reaction, and the unreacted small molecules will overflow in the form of gas, the volume of the solid material will shrink, and the performance (hardness, etc.) will improve.
[0026] Water bath magnetic stirring has good dispersion effect and temperature control accuracy, which can effectively control the reaction process and improve mixing uniformity.
[0027] After obtaining the mixed solution of the repair agent matrix material, TiB is added thereto. 2 It can make the three have good dispersion, ensuring TiB 2 Evenly distributed between the restorative matrix materials.
[0028] In some embodiments, the heat treatment process is: heating to 250-325°C at a rate of 2-4°C / min and keeping warm for 15-75 minutes; after the insulation is completed, heating to 900-1000°C at a rate of 4-8°C / min and keeping warm for 60-80 minutes.
[0029] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0030] The repair agent of the present invention can realize the transformation from liquid phase to solid phase during the repair process. When used, the liquid phase repair agent can more easily enter defect positions such as cracks and gaps. The repair process does not require atmosphere support and can realize the repair of the inside of the workpiece.
[0031] In the preparation method of the present invention, TiB is added 2 The particles can not only reduce the volume shrinkage of the repair agent and improve the mechanical properties of the repair agent, but also 2 It is added to the material to be repaired as a reinforcing phase to improve the repair effect.
[0032] The exogenous ceramic tool repair method adopted by the present invention does not need to add additional materials in the tool design, so it will not affect the tool material performance and will not increase the tool design steps.
[0033] The exogenous repair method for ceramic cutting tools of the present invention can be adapted to the repair of various ceramic cutting tool materials and is not limited by the components of the ceramic materials. In addition, since the heat treatment process of the repairing agent can be carried out in the air, the repair process can be applied to many scenarios.
[0034] The precursor ceramic adhesive repair agent of the present invention has a simple preparation process, low raw material cost and obvious repair effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0036] Figure 1 Schematic diagram of shear strength test in an embodiment of the present invention.
[0037] Figure 2 1 and 2 are repair morphology diagrams of Example 1 of the present invention, wherein (a) is a cross-sectional morphology diagram of the repaired position; and (b) is a surface morphology diagram of the repaired position.
[0038] Figure 3 For the repair morphology section ( Figure 2 EDS line scan at (a).
[0039] Figure 4 This is the XRD phase analysis of the repair agent in Example 1 of the present invention.
[0040] Figure 5 These are the repair morphology images in Example 2 of the present invention, (a) is a cross-sectional morphology image of the repaired position; (b) is a surface morphology image of the repaired position.
[0041] Figure 6 These are the repair morphology images in comparative example 1 of the present invention, (a) is a cross-sectional morphology image of the repaired position; (b) is a surface morphology image of the repaired position.
[0042] Figure 7These are the repair morphology images in comparative example 2 of the present invention, (a) is a cross-sectional morphology image of the repaired position; (b) is a surface morphology image of the repaired position.
[0043] Figure 8 For different TiB in each case of the present invention 2 Change trend of shear strength of repaired samples with different contents.
[0044] Fig. 9 is the contact angle of the precursor ceramic adhesive repair agent used in the present invention.
[0045] Fig.10 The repair morphology and element analysis diagram in Example 3 of the present invention, (a) is the repair morphology at the crack position, and (b) is the EDS line scan diagram of the crack area.
[0046] Fig.11 The repair morphology and element analysis diagram in Example 4 of the present invention, (a) is the repair morphology at the crack position, and (b) is the EDS line scan diagram of the crack area.
[0047] Fig.12 These are the repair morphologies and elemental analysis diagrams of Example 5 of the present invention, (a) is the repair morphology of the back tool face area, (b) is a local enlarged diagram of the repair morphology of the back tool face area, and (c) is the EDS elemental analysis of the repair morphology of the back tool face area.
[0048] Fig.13 The repair morphology and element analysis diagram of comparative example 3 of the present invention, (a) is the repair morphology at the crack position, and (b) is the EDS line scan diagram of the crack area.
[0049] Fig.14 The repair morphology and element analysis diagram of comparative example 4 of the present invention, (a) is the repair morphology at the crack position, and (b) is the EDS line scan diagram of the crack area.
[0050] Fig.15 This is a comparison chart of the effect of repair temperature on the flexural strength of repaired ceramic specimens in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0051] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0052] The present invention will be further described below in conjunction with the embodiments.
[0053] PMHS solution was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. The purity of PMHS was 98.5%, the number average molecular weight was 1700-3200, and the hydrogen content was 1.6%;
[0054] D 4 Vi solution was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. The purity of D4Vi was 95% and the density was 0.997 g / ml.
[0055] Example 1
[0056] A precursor ceramic adhesive repair material, comprising PMHS 40wt.%, D 4 Vi40wt.%, nano-TiB 2 20wt.%.
[0057] Weigh PMHS solution and D according to the ratio 4 Vi solution and TiB 2 Powder, PMHS solution and D 4 The Vi solutions were mixed and magnetically stirred for 20 min at a water bath temperature of 25° C. to obtain a matrix material of a precursor ceramic adhesive repair agent.
[0058] TiB is gradually added to the repair agent matrix material during the stirring process. 2 The powder was prepared and magnetic stirring was continued for 30 min at a water bath temperature of 25°C to obtain a precursor ceramic adhesive repair agent.
[0059] The precursor ceramic adhesive repair agent is evenly coated on the surface of alumina ceramic blocks A and B, where the size of ceramic block A is 10mm×10mm×4mm, and the size of ceramic block B is 20mm×10mm×4mm. The repair agent is respectively coated on the 10mm×10mm surface of ceramic block A and the 20mm×10mm surface of ceramic block B. The two surfaces coated with the repair agent are bonded together, and ensure that ceramic block A is in the middle position of ceramic block B.
[0060] The prepared ceramic sample was placed in a ceramic crucible and then placed in a muffle furnace for heat treatment according to the following parameters: the temperature was raised from 25°C to 300°C at 3°C / min and kept at this temperature for 60 minutes; after the holding time, the temperature was raised to 900°C at 5°C / min and kept at this temperature for 60 minutes. The obtained sample was tested and characterized, and the results showed that its shear strength was 16.3MPa and the surface morphology was as follows: Figure 2 As shown in the figure, the repair agent at the gap is relatively dense, there is no obvious gap defect, and the repair agent composition is uniform, and the repair effect is the best; Figure 3 It can be seen that the content of Ti, Si and O elements increases, and the content of Al element decreases at the gap position. Figure 4 From the XRD image, it can be seen that the crystal phase of the repaired material is TiB 2 , the amorphous phase includes SiC 2 O 6 、SiC、(SiO2 ) x (CH 4 ) y 、(SiO 2 ) x (C 3 H 6 O 3 ) y and a small amount of free carbon are the main products after pyrolysis of the repair agent.
[0061] Example 2
[0062] A precursor ceramic adhesive repair material, comprising 35wt.% PMHS, D 4 Vi35wt.%, nano-TiB 2 30wt.%.
[0063] Weigh PMHS solution and D according to the ratio 4 Vi solution and TiB 2 Powder, PMHS solution and D 4 The Vi solutions were mixed and magnetically stirred for 20 min at a water bath temperature of 25° C. to obtain a matrix material of a precursor ceramic adhesive repair agent.
[0064] TiB is gradually added to the repair agent matrix material during the stirring process. 2 The powder was prepared and magnetic stirring was continued for 30 min at a water bath temperature of 25°C to obtain a precursor ceramic adhesive repair agent.
[0065] The precursor ceramic adhesive repair agent is evenly coated on the surface of alumina ceramic blocks A and B, where the size of ceramic block A is 10mm×10mm×4mm, and the size of ceramic block B is 20mm×10mm×4mm. The repair agent is respectively coated on the 10mm×10mm surface of ceramic block A and the 20mm×10mm surface of ceramic block B. The two surfaces coated with the repair agent are bonded together, and ensure that ceramic block A is in the middle position of ceramic block B.
[0066] The prepared ceramic sample was placed in a ceramic crucible and then placed in a muffle furnace for heat treatment according to the following parameters: the temperature was raised from 25°C to 300°C at 3°C / min and kept at this temperature for 60 minutes; after the holding time, the temperature was raised to 900°C at 5°C / min and kept at this temperature for 60 minutes. The obtained sample was tested and characterized, and the results showed that its shear strength was 13.34MPa and the surface morphology was as follows: Figure 5 As shown, there are a few gaps in the repaired area, accompanied by TiB 2 There is a phenomenon of particle agglomeration, but there are more filling and repair positions and the repair effect is better.
[0067] Comparative Example 1
[0068] A precursor ceramic adhesive repair material, comprising 45wt.% PMHS, D 4 Vi45wt.%, nano-TiB 2 10wt.%.
[0069] Weigh PMHS solution and D according to the ratio 4 Vi solution and TiB 2 Powder, PMHS solution and D 4 The Vi solutions were mixed and magnetically stirred for 20 min at a water bath temperature of 25° C. to obtain a matrix material of a precursor ceramic adhesive repair agent.
[0070] TiB is gradually added to the repair agent matrix material during the stirring process. 2 The powder was prepared and magnetic stirring was continued for 30 min at a water bath temperature of 25°C to obtain a precursor ceramic adhesive repair agent.
[0071] The precursor ceramic adhesive repair agent is evenly coated on the surface of alumina ceramic blocks A and B, where the size of ceramic block A is 10mm×10mm×4mm, and the size of ceramic block B is 20mm×10mm×4mm. The repair agent is respectively coated on the 10mm×10mm surface of ceramic block A and the 20mm×10mm surface of ceramic block B. The two surfaces coated with the repair agent are bonded together, and ensure that ceramic block A is in the middle position of ceramic block B.
[0072] The prepared ceramic sample was placed in a ceramic crucible and then placed in a muffle furnace for heat treatment according to the following parameters: the temperature was raised from 25°C to 300°C at 3°C / min and kept at this temperature for 60 minutes; after the holding time, the temperature was raised to 900°C at 5°C / min and kept at this temperature for 60 minutes. The obtained sample was tested and characterized, and the results showed that its shear strength was 13.14MPa and the surface morphology was as follows: Figure 6 As shown in the figure, there are obvious gaps in the repaired position, and the repair agent is less filled, and the repair effect is poor. This is because TiB 2 Fillers can reduce the volume shrinkage of the repair agent matrix. When the filler content is low, the repair agent still has obvious volume shrinkage after the reaction, resulting in poor bonding with the ceramic material and poor repair effect.
[0073] Comparative Example 2
[0074] A precursor ceramic adhesive repair material, comprising 30wt.% PMHS, D 4 Vi30wt.%, nano-TiB 2 40wt.%.
[0075] Weigh PMHS solution and D according to the ratio 4 Vi solution and TiB 2Powder, PMHS solution and D 4 The Vi solutions were mixed and magnetically stirred for 20 min at a water bath temperature of 25° C. to obtain a matrix material of a precursor ceramic adhesive repair agent.
[0076] TiB is gradually added to the repair agent matrix material during the stirring process. 2 The powder was prepared and magnetic stirring was continued for 30 min at a water bath temperature of 25°C to obtain a precursor ceramic adhesive repair agent.
[0077] The precursor ceramic adhesive repair agent is evenly coated on the surface of alumina ceramic blocks A and B, where the size of ceramic block A is 10mm×10mm×4mm, and the size of ceramic block B is 20mm×10mm×4mm. The repair agent is respectively coated on the 10mm×10mm surface of ceramic block A and the 20mm×10mm surface of ceramic block B. The two surfaces coated with the repair agent are bonded together, and ensure that ceramic block A is in the middle position of ceramic block B.
[0078] The prepared ceramic sample was placed in a ceramic crucible and then placed in a muffle furnace for heat treatment according to the following parameters: heating from 25°C to 300°C at 3°C / min and keeping warm for 60 minutes; after the holding time, heating to 900°C at 5°C / min and keeping warm for 60 minutes.
[0079] The obtained sample was tested and characterized, and the results showed that its shear strength was 12.11MPa and the surface morphology was as follows: Figure 7 As shown, the repaired area is mainly TiB 2 Particles, and the bonding between the repair agents in the gaps is loose, and there are obvious gaps, indicating that the filler has been added excessively and the repair effect is the worst.
[0080] Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are respectively prepared by adding different contents of TiB to the repair agent matrix (ie, PMHS and D4Vi are mixed in a mass ratio of 1:1). 2 Fillers (20wt.%, 30wt.%, 10wt.%, 40wt.%), tested for their bonding to Al 2 O 3 The shear strength and morphology of the ceramic block. The conclusion is that 20wt.% has the best effect, and the following examples and comparative examples are all carried out at this content.
[0081] Example 3
[0082] The repair performance of the exogenous repair method at different temperatures was tested by the indentation method to pre-crack. The specific steps include:
[0083] Al 2 O 3 / TiC / NiMo ceramic tool material was cut into 3mm×4mm×30mm strip specimens, and a load was applied at the center of any 4mm×30mm surface by the indentation method, where the indenter load was 196N and the holding time was 15s to obtain a specimen with a crack defect.
[0084] The sample was placed in the repair agent prepared in Example 1 and magnetically stirred in a 25°C water bath for 20 minutes to ensure that the repair agent could enter the crack. The sample and the repair agent were then transferred to a crucible and placed in a muffle furnace for a heat treatment experiment. The heating parameters were:
[0085] The temperature was raised from 25°C to 300°C at a rate of 3°C / min and kept at that temperature for 60 min. After the heat preservation, the temperature was raised to 800°C at a rate of 5°C / min and kept at that temperature for 60 min.
[0086] The repaired samples were ground and polished, and their repair morphology was characterized and mechanical properties were tested. The results showed that the bending strength was 396.5MPa and the surface of the crack after repair was as follows: Fig.10 As shown in the figure, it can be seen that at this temperature, the repair agent is tightly combined with the ceramic material, but there is still a relatively obvious crack area, which is caused by the volume shrinkage of the repair agent at high temperature. From the EDS line scan, it can be seen that the repair agent plays a major role in the crack repair process, and the repair effect is good.
[0087] Example 4
[0088] The repair performance of the exogenous repair method at different temperatures was tested by the indentation method to pre-crack. The specific steps include:
[0089] Al 2 O 3 / TiC / NiMo ceramic tool material was cut into 3mm×4mm×30mm strip specimens, in which NiMo metal accounted for 4wt.%, Ni:Mo=2:1, and a load was applied at the center of any 4mm×30mm surface by the indentation method, in which the indenter load was 196N and the holding time was 15s to obtain a specimen with a crack defect.
[0090] The repair agent has a very small contact angle of about 8.9° on the surface of the ceramic material, which can ensure that the repair agent enters the crack area.
[0091] The sample was placed in the repair agent prepared in Example 1 and magnetically stirred in a 25°C water bath for 20 minutes to ensure that the repair agent could enter the crack. The sample and the repair agent were then transferred to a crucible and placed in a muffle furnace for a heat treatment experiment. The heating parameters were:
[0092] The temperature was raised from 25°C to 300°C at a rate of 3°C / min and kept at that temperature for 60 min. After the heat preservation, the temperature was raised to 900°C at a rate of 5°C / min and kept at that temperature for 60 min.
[0093] The repaired samples were ground and polished, and their repair morphology was characterized and the mechanical properties were tested.
[0094] Grinding and polishing the heat-treated specimens can remove the repair material on the surface of the specimens, reducing its influence on the results during the test. In addition, it can also facilitate the observation of the repair morphology of the crack position. The particle size of the grinding paste is W5, and the particle size of the polishing agent is W2.5.
[0095] The results show that its bending strength is 456.5MPa (test span is 20mm, load application speed is 0.5mm / min), and the surface after crack repair is as follows Fig.11 As shown, it can be seen that with the increase of the repair temperature, the repair effect of the repair agent on the crack is better, the crack position has been completely filled, and there is no obvious crack mark on the surface of the sample, and the repair effect is the best.
[0096] Example 5
[0097] The surface wear of ceramic tools is repaired by exogenous repair method, which specifically includes the following steps:
[0098] Al 2 O 3 The / TiC / NiMo ceramic tool material was cut into standard turning tool specimens of 13mm×13mm×5mm, in which the NiMo metal accounted for 4wt.%, and Ni:Mo=2:1. The specimens were subjected to rough grinding, chamfering, grinding and polishing before cutting experiments.
[0099] The repair agent has a very small contact angle of about 8.9° on the surface of the ceramic material, which can ensure that the repair agent enters the crack area.
[0100] The cutting workpiece is 304 stainless steel, and the cutting parameters are: cutting speed v c =200m / min, back cutting amount a p =0.1mm, feed rate f=0.1mm / r, and use an ultra-depth-of-field microscope to observe the flank wear of the ceramic tool every 200m of cutting. When the wear distance reaches about 0.25mm, the ceramic tool is removed.
[0101] The tool sample was placed in the repair agent prepared in Example 1 and magnetically stirred in a 25°C water bath for 20 min. The tool sample and the repair agent were then transferred to a crucible and placed in a muffle furnace for a heat treatment experiment. The heating parameters were:
[0102] The temperature was raised from 25°C to 300°C at 3°C / min and kept at this temperature for 60 min. After the temperature was raised to 900°C at 5°C / min and kept at this temperature for 60 min.
[0103] After grinding and polishing the repaired sample, the cutting experiment was continued with the above cutting parameters to observe the wear of the flank face. The results show that after one repair experiment, the cutting distance can be extended to 1700m, which is about 400m longer. Fig.12 As shown in the figure, it can be seen that after the repair experiment, the repair agent can fill and repair the chipping position of the back tool face, restore the original tool morphology, and replace the ceramic tool for cutting, thereby extending the tool cutting life. From the partial enlarged picture, it can be seen that the repair agent can slow down the expansion of the crack and repair the crack. Combined with the element analysis, it can be seen that the filling elements of the chipping position are mainly Si, C and Ti elements, and the wear form after repair is mainly abrasive wear and adhesive wear.
[0104] Comparative Example 3
[0105] The repair performance of the exogenous repair method at different temperatures was tested by the indentation method to pre-crack. The specific steps include:
[0106] Al 2 O 3 / TiC / NiMo ceramic tool material was cut into 3mm×4mm×30mm strip specimens, and a load was applied at the center of any 4mm×30mm surface by the indentation method, where the indenter load was 196N and the holding time was 15s to obtain a specimen with a crack defect.
[0107] The sample was placed in the repair agent prepared in Example 1 and magnetically stirred in a 25°C water bath for 20 minutes to ensure that the repair agent could enter the crack. The sample and the repair agent were then transferred to a crucible and placed in a muffle furnace for a heat treatment experiment. The heating parameters were:
[0108] The temperature was raised from 25°C to 300°C at a rate of 3°C / min and kept at that temperature for 60 min. After the heat preservation, the temperature was raised to 600°C at a rate of 5°C / min and kept at that temperature for 60 min.
[0109] The repaired samples were ground and polished, and their repair morphology was characterized and mechanical properties were tested. The results showed that the bending strength was 163.5MPa and the surface of the crack after repair was as follows: Fig.13 As shown, it can be seen that there is still an obvious gap between the repair agent and the ceramic material, which is the main reason for the poor improvement of mechanical properties and the worst repair effect.
[0110] Comparative Example 4
[0111] The repair performance of the exogenous repair method at different temperatures was tested by the indentation method to pre-crack. The specific steps include:
[0112] Al 2 O 3 / TiC / NiMo ceramic tool material was cut into 3mm×4mm×30mm strip specimens, and a load was applied at the center of any 4mm×30mm surface by the indentation method, where the indenter load was 196N and the holding time was 15s to obtain a specimen with a crack defect.
[0113] The sample was placed in the repair agent prepared in Example 1 and magnetically stirred in a 25°C water bath for 20 minutes to ensure that the repair agent could enter the crack. The sample and the repair agent were then transferred to a crucible and placed in a muffle furnace for a heat treatment experiment. The heating parameters were:
[0114] The temperature was raised from 25°C to 300°C at a rate of 3°C / min and kept at that temperature for 60 min. After the heat preservation, the temperature was raised to 700°C at a rate of 5°C / min and kept at that temperature for 60 min.
[0115] The repaired samples were ground and polished, and their repair morphology was characterized and mechanical properties were tested. The results showed that the bending strength was 162.3MPa. Fig.14 As shown, it can be seen that there is no gap between the repair agent and the ceramic material, indicating that the combination between the two is good; but there is still a small amount of repair agent falling off, indicating that the performance of the repair agent itself is not good at this temperature. In addition, it can be seen that the crack marks are still very obvious and the repair effect is poor.
[0116] Fig.15 This is a comparison chart of the effect of the repair temperature on the flexural strength of the repaired ceramic specimens in the above embodiments and comparative examples. It can be seen that when the repair temperature is 800°C and 900°C, or even 900°C and above, better repair effects can be achieved.
[0117] Comparative Example 5
[0118] The service life of the ceramic tool surface after repair by comparing the exogenous repair method includes the following steps:
[0119] Al 2 O 3 The / TiC / NiMo ceramic tool material was cut into standard turning tool specimens of 13mm×13mm×5mm, and the cutting experiment was carried out after the specimens were roughly ground, chamfered, ground and polished.
[0120] The cutting workpiece is 304 stainless steel, and the cutting parameters are: cutting speed v c=200m / min, back cutting amount a p =0.1mm, feed rate f=0.1mm / r, and use ultra-depth microscope to observe the wear of the ceramic tool back face every 200m of cutting, until the wear distance exceeds 0.3mm and the experiment is stopped. The results show that the cutting distance is 1300m.
[0121] The purpose of this comparative example is to obtain the cutting life of the tool without repair.
[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A precursor ceramic adhesive repair agent, characterized in that: By mass, it is composed of the following components: PMHS 25-75 parts, D 4 Vi 25-75 parts, nano-TiB2 12-38 parts.
2. The precursor ceramic adhesive repair agent according to claim 1, characterized in that: By mass, it includes the following components: PMHS 30-60 parts, D 4 Vi 30-60 parts, nano-TiB2 15-35 parts.
3. The precursor ceramic adhesive repair agent according to claim 2, characterized in that: By mass, it includes the following components: PMHS 30-50 parts, D 4 Vi 30-50 parts, nano-TiB2 15-30 parts.
4. The precursor ceramic adhesive repair agent according to claim 3, characterized in that: By mass, it includes the following components: PMHS 35-45 parts, D 4 Vi 35-45 parts, nano-TiB2 15-25 parts.
5. The precursor ceramic adhesive repair agent according to claim 4, characterized in that: The precursor ceramic adhesive repair agent comprises the following components by weight: 40 parts of PMHS, D 4 Vi 40 parts, nano-TiB2 20 parts.
6. The precursor ceramic adhesive repair agent according to any one of claims 1 to 5, characterized in that: The number average molecular weight of PMHS is 1700-3200.
7. The precursor ceramic adhesive repair agent according to any one of claims 1 to 5, characterized in that: The average particle size of TiB2 powder is 40nm.
8. The method for preparing the precursor ceramic adhesive repair agent according to any one of claims 1 to 7, characterized in that: The steps include: PMHS and D 4 Vi are mixed evenly according to the proportion to obtain a matrix mixed liquid; Add nano-TiB2 into the matrix mixed solution, mix well, and obtain the repair agent.
9. A repair method using the precursor ceramic adhesive repair agent according to any one of claims 1 to 7, characterized in that: The steps include: The repairing agent is applied to the repaired position of the ceramic workpiece to be repaired, so that the repairing agent penetrates into the damaged interior; and then the workpiece to be repaired is heat treated to complete the repair; The heat treatment process is: heating to 250-325°C at a rate of 2-4°C / min and keeping the temperature for 15-75min; After the insulation is completed, the temperature is raised to 800-1500°C at a rate of 4-8°C / min and maintained for more than 60 minutes.
10. The repair method of the precursor ceramic adhesive repair agent according to claim 9, characterized in that: The heat treatment process is: heating to 250-325°C at a rate of 2-4°C / min and keeping the temperature for 15-75min; After the insulation is completed, the temperature is raised to 900-1000°C at a rate of 4-8°C / min and maintained for 60-80 minutes.
Citation Information
Patent Citations
A ceramic adhesive and a preparing method thereof
CN104163635A
Self-repairing ceramic silicone rubber material and preparation method thereof
CN110183858A
High-strength aluminum alloy laser additive repairing method based on multi-dimensional stress regulation and control
CN116809959A
Ceramic-based high-toughness high-temperature binder and method for improving performance of ceramic-based high-toughness high-temperature binder
CN117801771A
Raw material for burned body and manufacturing method of burned body
JP2017128465A